Copa do mundo de futebol de 1950: critérios de noticiabilidade e análise de conteúdo da cobertura realizada pelo jornalismo de revista brasileiro - Penariol, Júlio César [UNESP] (2015)
This study aims to analyze the coverage of the sporting event, and check as weekly magazines aimed at different audiences portrayed the sporting event. The corpus of the research encompasses the material produced by four weekly magazines of that time - Revista da Semana, Careta, fon-fon! and O Cruzeiro - between 1 january 1950 and 31 August of the same year, which is nearly six months before the start of the World and more that a month after the dispute of the last round. Even with readership and content different from each other, are the four publications build a converged discourse on one sporting event in the euphoria and exaltation of all that was related to the country are present in the texts? That's the question we want to answer. After all, the World Cup was a chance that Brazil had to show the world how a civilized, developed and modern nation, and organize a football competitionof this size was a key to achieve this goal. On the other hand, the unexpected defeat of the Brazilian team in the final game against Uruguay, and involving the loss of the title before more than 200,000 fans of the giant Maracana stadium, seems to change the tone of the press part of speech. The failure of the field team brings back synonyms linked to the country and that the would like to hide from foreign nations - and himself - such as underdevelopment, sadness and poverty